THE EFFECT OF RAMANIA LEAF (Bouea macrophylla Griff) EXTRACT GEL ON THE NUMBER OF FIBROBLAST CELLS OF INCISION IN MALE WISTAR RATS (Rattus norvegicus) - Salma Humaira; Irham Taufiqurrahman; Nurdiana Dewi (FKG Unlam, 2022)
Background: Ramania leaf (Bouea macrophylla Griff) extract gel has secondary metabolites in the form of flavonoids, steroids, phenols and terpenoids which have potential as an adjuvant therapy for wound healing. Flavonoid can act as immunomodulators and activate macrophages which will release growth factors and stimulate proliferation of fibroblasts resulting in an increase number of fibroblasts. Objective: To analyze the effect of ramania leaf (Bouea macrophylla Griff) extract gel on the number of fibroblast cells of incision in male wistar rats. Methods: This research was a true experimental method with a posttestonly with control group design, using 24 rats which divided into 4 groups: the treatment groups which were given ramania leaf extract gel with the concentrations of 5%, 10%, 15% and the control group which were given placebo gel. Tissue retrieval was done for the process of histopathological observation. Results: The results of two-way ANOVA test obtained p value = 0.640 > 0.05 which showed no significant difference between the use of ramania leaf extract gel on the number of fibroblasts on the 7th and 14th days. The Post Hoc Bonferroni test showed a significant difference in the number of fibroblasts between the control group and the group of ramania leaves extract gel concentration of 15%. Conclusion: Ramania leaf extract gel has the ability to increase the number of fibroblast cells and has potential as an adjuvant therapy for wound healing with the most effective concentration of 15%.